2014
DOI: 10.1103/physreva.89.052707
|View full text |Cite
|
Sign up to set email alerts
|

Full-correlation single-particle positron potentials for a positron and positronium interacting with atoms

Abstract: In this work we define single-particle potentials for a positron and a positronium atom interacting with light atoms (H, He, Li and Be) by inverting a single-particle Schrödinger equation. For this purpose, we use accurate energies and positron densities obtained from the many-body wavefunction of the corresponding positronic systems. The introduced potentials describe the exact correlations for the calculated systems including the formation of a positronium atom. We show that the scattering lengths and the lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
(66 reference statements)
1
24
0
Order By: Relevance
“…Zubiaga et al . [27,18,36] have used ECG-SVM and external confining potentials to study unbound positronic systems including e + H, e + He and specially HePs. By choosing a large enough confinement radius, the wavefunction could be calculated accurately in the interaction region.…”
Section: Many-body Calculations For the Psmentioning
confidence: 99%
“…Zubiaga et al . [27,18,36] have used ECG-SVM and external confining potentials to study unbound positronic systems including e + H, e + He and specially HePs. By choosing a large enough confinement radius, the wavefunction could be calculated accurately in the interaction region.…”
Section: Many-body Calculations For the Psmentioning
confidence: 99%
“…Instead it has a shallow attractive well for separations from the nucleus of 1.3 a.u. [12]. We consider now low energy Ps scattering off He in order to study the adequacy of V Ps eff to model Ps states.…”
Section: Single-particle Interaction Potentialsmentioning
confidence: 99%
“…The formally exact expression for the TD electron-positron correlation functional is then derived by extending the TDDFT action principle [29] to a MC system. Furthermore, we introduce the adiabatic local density approximation (ALDA) to the TD electron-positron correlation, and adopt the ground-state electron-positron correlation energy functional within the LDA [15]. Finally, the TDM-CDFT method is applied to the dynamics of a positronic lithium hydride (e + -LiH) molecule under a laser field and elucidate the significant role of TD electron-positron correlation in their coupled dynamics.…”
mentioning
confidence: 99%
“…Specifically, the LDA [33] is used for E − xc . For E −+ c , we also use the LDA parameterized by Puska et al, which has been reported to be suitable for the ground state of positronic atoms [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation